Efflux pump of the proton antiporter family confers low-level fluoroquinolone resistance in Mycobacterium smegmatis. - Takiff, H E (1996)
Due to the resurgence of tuberculosis and the emergence of multidrug-resistant strains, fluoroquinolones (FQ) are being used in selected tuberculosis patients, but FQ-resistant strains of Mycobacterium tuberculosis have rapidly begun to appear. The mechanisms involved in FQ resistance need to be elucidated if the effectiveness of this class of antibiotics is to be improved and prolonged. By using the rapid-growing Mycobacterium smegmatis as a model genetic system, a gene was selected that confers low-level FQ resistance when present on a multicopy plasmid. This gene, lfrA, encodes a putative membrane efflux pump of the major facilitator family, which appears to recognize the hydrophilic FQ, ethidium bromide, acridine, and some quaternary ammonium compounds. It is homologous to qacA from Staphylococcus aureus, tcmA, of Streptomyces glaucescens, and actII and mmr, both from Streptomyces coelicoler. Increased expression of lfrA augments the appearance of subsequent mutations to higher-level FQ resistance.